2002
DOI: 10.1128/mcb.22.14.5128-5140.2002
|View full text |Cite
|
Sign up to set email alerts
|

H-Ras Signaling and K-Ras Signaling Are Differentially Dependent on Endocytosis

Abstract: Endocytosis is required for efficient mitogen-activated protein kinase (MAPK) activation by activated growth factor receptors. We examined if H-Ras and K-Ras proteins, which are distributed across different plasma membrane microdomains, have equal access to the endocytic compartment and whether this access is necessary for downstream signaling. Inhibition of endocytosis by dominant interfering dynamin-K44A blocked H-Ras but not K-Ras-mediated PC12 cell differentiation and selectively inhibited H-Ras-but not K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 71 publications
9
118
2
Order By: Relevance
“…[8] More recently, thanks to the pioneering work of M. Philips, it was demonstrated that Ras was also present and active in endomembranes like the endoplasmic reticulum (ER) and the Golgi complex (GC). [9,10] The three Ras isoforms were also detected in endosomes [11,12] and mitochondria [13][14][15] (for a review see ref. 16).…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] More recently, thanks to the pioneering work of M. Philips, it was demonstrated that Ras was also present and active in endomembranes like the endoplasmic reticulum (ER) and the Golgi complex (GC). [9,10] The three Ras isoforms were also detected in endosomes [11,12] and mitochondria [13][14][15] (for a review see ref. 16).…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
“…[29] Interestingly, Ras association to endosomes exhibits isoform specificity: whereas N-and H-Ras establish stable interactions with the endosomal compartment, K-Ras does not. [11,30,31] These differences have been attributed to the modification of N-and H-Ras, but not of K-Ras, by ubiquitination. [31] At the PM, Ras proteins partition into microdomains referred to as ''nanoclusters.''…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
“…Growth factor receptor endocytosis is necessary for efficient activation of the Raf-MAPK cascade and promotion of differentiation versus proliferation [104]. Isoform-specific signalling was seen when inhibition of dynamin dependent endocytosis selectively inhibited oncogenic H-Ras but not K-Ras activation of Raf [69]. Mitochondria have also been identified as sites of Ras activation.…”
Section: Compartmentalised Ras Signallingmentioning
confidence: 99%
“…[57][58][59] The fact that p120GAP remains associated with EGFR in endosomes 60 is another indication for the involvement of GAPs in the regulation of spatiotemporal Ras signaling, as active H-Ras is internalized with EGFR after stimulation. 45 The targeting protein for p120GAP, AnxA6, is also found in endosomes and able to bind active H-Ras. 30,39,40 Altogether, this could ensure H-Ras signal termination both at the plasma membrane and in early endosomes upon EGFR activation.…”
Section: Subcellular Localization Of Ras Signaling Complexesmentioning
confidence: 99%
“…NRas-GTP is mainly found in cholesterolsensitive membrane domains. It was initially believed that Ras signaling occurs exclusively at the plasma membrane, but since the discovery of active Ras in the endoplasmic reticulum and Golgi complex, 43,44 all 3 Ras isoforms have been detected in endosomes [45][46][47] and mitochondria. [48][49][50] Thus, Ras isoforms cannot be considered stationary but translocate between cellular compartments.…”
Section: Subcellular Localization Of Ras Signaling Complexesmentioning
confidence: 99%